Reparando Erros: o panorama em evolução das reparações e acordos por violações de direitos humanos - Garcia Garcia, Adriana; Lisitsyna, Masha (Unisanta Law and Social Science, 2025)
As an integral component of justice for victims of human rights violations, reparations hold a pivotal role in both international and national legal frameworks. This prominence is reflected in over 60 global federal constitutions, each advocating for victims’ rights to reparations. Despite an increased clarity surrounding these rights, their practical execution remains a topic of ongoing discussion and evolution. This paper presents an opportunity to delve into this nuanced field, exploring reparations at the domestic levels. The paper illuminates the multifaceted nature of reparations, spanning from judicial proceedings to quasi-judicial mechanisms such as settlements and reparations programs. It explores the varying practices across different mechanisms and underscores the role of legal action as a catalyst for governments to offer settlements or reparations packages. Through real-world examples, such as the struggles of the Herrero and Nama tribes in Namibia or the injustices faced by indigenous children in Canada, the journey towards justice and the critical role of judicial reparations are brought to life. The paper further sheds light on the emerging trend of courts ordering non-repetition measures, particularly evident in Latin America and South Asia. It delves into the complexities of settlements in human rights violation cases, including the controversial yet impactful mechanisms like consent decrees in the United States. While there is an abundance of literature on reparations programs, a significant gap exists when it comes to domestic judicial reparations and settlements. This paper seeks to bridge that gap, showcasing innovative judgments and agreements from around the globe. Although not exhaustive, the research presented provides intriguing insights into how courts are addressing these critical issues. Readers are invited to embark on this exploration of judicial reparations, to understand their importance, and to engage in the discussion about their future direction.